Perbaikan Rute Distribusi Bahan Baku untuk Minimasi Jarak Tempuh dan Beban Kerja pada UKM Kuliner Mie - Lisa Amanda Link; Fransiska Hernina Puspitasari; Parama Kartika Dewa (OPSI, 2022)
Delivery activities have a great role for a business actor. However, delivery issues are there all the time. This was experienced by a noodle culinary SME that experienced delays in the delivery of various noodle raw materials and noodle toppings which caused noodle sales activities to be disrupted. In addition, these raw materials have a lifespan (without preservatives) so they must be delivered according to a predetermined schedule and hours. This research will solve this problem by minimizing delays through finding the shortest mileage delivery route. Because each delivery location has its own schedule and time window, the Nearest Neighbor method by paying attention to the time window is used. Based on the calculation results, each distribution route with the shortest distance was obtained, as evidenced by a reduction in the middle route by 0.23 km and the northern route by 5.88 km. In addition, this proposed delivery route was able to save fuel consumption on the middle route by 3% and the northern route by 10%. In terms of the workload aspect, car fleet drivers were also reduced by 31% and motorbike fleet drivers by 47%.